Efectos de la herbivoría sobre la cantidad de óvulos en Loasa speciosa (Loasaceae) - Gramacho, Milena; Santander, Tatiana; Farji-Brener, Alejandro G (Revista de Biología Tropical, 2001)
We examined the direct effect of foliar herbivory on female fitness in the herbaceous plant Loasa speciosa (Loasaceae), measuring ovule number/flower in 46 shoots with different levels of leaf damage. Ovule number/flower was lower in shoots with higher herbivory levels. This result suggests that the known negative impact of herbivory on female plant fitness (i.e. low seed number) can be a direct consequence of the reduction of ovule number.